Peran Satuan Intelkam Dalam Mencegah Paham Radikal di Masyarakat Melalui Deradikalisasi (Studi Pada Satuan Intelkam Polres Deli Serdang. - Rahmad Hutagaol (Universitas Islam Sumatera Utara, 2020)
Deli Serdang Resort Police Jurisdiction has done its role in effort to image and develop radical understanding to the community by involving all components as well as de-radicalizing groups or people who have committed radical/ terrorist act so that the group or person is aware of their mistakes and omission for action that can harm the integrity of the nation and state. In addition to this, Deli Serdang Resort Police also conducted various de-radicalization programs.The problem formulated in the formulation of the problem is how Deli Serdang Resort Police Intelligence Unit plays a role in preventing radical understanding through de-radicalization. What are the efforts made by Deli Serdang Resort Police Intelligence Unit in preventing radical understanding through de-radicalization? Are there obstacles in Deli Serdang Resort Police Intelligence Unit in preventing radical ideology through de-radicalization? The approach taken is to use the normative juridical method. The juridical normative approach method is used to examine library materials which are primary data. Based on the data obtained, then an analysis is done to draw conclusion after being described in detail based on available sources.The results of this study are the role of Deli SerdangResort Police Intelligence Unit in preventing radical understanding through de-radicalization.The role of Deli Serdang Resort Police Intelligence Unit is to monitor the movement of the community and community groups so that they do not follow radical ideas, provide counseling, conduct communityand religious activities. Efforts made by Deli Serdang Resort Police Intelligence Unit in preventing radical ideology through de-radicalism are to provide guidance to people or groups who have already been serving sentences for carrying out radical actions in the family, then detecting various community activities that lead to radical understanding, provide counseling with religious and community leaders. The obstacles of Deli Serdang Resort Police Intelligence Unit in preventing radical understanding through de-radicalization being are the lack of budget for detecting and counseling among the community. Key-words : Intelligence Unit, Radical Understanding, Public